El Marcel Bataillon 'civil' y su compromiso intelectual con España y América - Herrero, Ana Vian (El Colegio de México, 2011)
In this paper, the author makes a careful reading of the book of ClaudeBataillon (Marcel Bataillon, hispanisme et engagement. Lettres, carnets et textesretrouvés [1914-1967], published in 2009). The analyzed text provides importantdetails that reveal the intellectual and moral commitment of Bataillon,which are, in the opinion of the author, barely known. It is, therefore,a book that deserves to be read and savored by all Hispanists. To integratethe image of Bataillon as a civilian with the one of him as an enormous anddelicate philologist and historian is prophylactic in this hour of disappointmentand neglect.